Comparison of disc-diffusion and disc-volatilization assays for determining the antimicrobial activity of Thymus vulgaris L. essential oil - Ignatiuk, Katarzyna; Dzikon, Ewelina; Hagdej, Brygida; Slotwinska, Weronika; Malm, Maria; Ossowski, Mateusz; Kasela, Martyna (Current Issues in Pharmacy and Medical Sciences, 2023)
Essential oils (EOs), being mixtures of various natural compounds, constitute an attractive source of novel antimicrobial agents. Along with multiple studies concerning their rich biological activity, there are different methods allowing to determine both antimicrobial activity in direct contact, as well as through the activity of vapours. Thyme constitutes one of the most common aromatic herbs used for pharmaceutical, cosmetic and culinary purposes. The aim of the study was to compare the antibacterial activity of liquid and vapour phases of Thymus vulgaris L. essential oil (TEO) against most common pathogenic Gram-positive (Staphylococcus aureus ATCC 25913, Enterococcus faecalis ATCC 29212, Bacillus cereus ATCC 10876) and Gram-negative (Escherichia coli ATCC 25922, Salmonella typhimurium ATCC 14028, Pseudomonas aeruginosa ATCC 27853) microorganisms. To determine TEO antibacterial properties, two methods were used: disc-diffusion assay so as to test activity in direct contact; disc-volatilization assay so as to determine activity in gaseous contact. Statistical analysis showed that Gram-positive bacteria were more sensitive to TEO vapours than Gram-negative (p=0.005), while in the case of disc-diffusion assay, no such differences were evident. Moreover, sensitivity towards TEO differed among Gram-positive bacteria in disc-diffusion (p=0.009) and disc-volatilization assay (p=0.001). Among Gram-negative rods, a statistically higher sensitivity regarding E. coli was noted when compared to S. typhimurium in both direct (p=0.011) and gaseous (p=0.006) TEO contact. No activity of TEO against P. aeruginosa was found. As thyme essential oil exhibited significant antimicrobial activity against Gram-positive bacteria in gaseous contact, this justifies its use as an addition to inhalation agents to prevent or support the treatment of upper respiratory tract infections. Further studies should therefore apply other methods for determining the antibacterial activity of TEO vapours to assess the exact minimal concentration inhibiting bacterial growth.